SISTEM TULISAN JAWI DALAM MANUSKRIP HIKAYAT RAJA HANDAK MS172 (1832M) (Jawi Writing System in the Manuscripts of Hikayat Raja Handak MS172 (1832M)) - Abdul Hamid, Faisal @ Ahmad Faisal (Journal of Al-Tamaddun, 2019)
This article describes Jawi writing system in the early 19th century. Manuscript Hikayat Raja Handak was selected as a sample of the study to get a description of what the Jawi writing system was at that time. The manuscript is numbered MS172 in the library of the University of Malaya, Kuala Lumpur. This article discusses two things (1) a brief background on this manuscript and (2) analyzing the Jawi writing system contained in the manuscript. Method of analysis used is a descriptive method based on 12 items that can describe the writing system, including the use of consonant, diftong, prefixes or suffixes and foreign languages such as Arabic. From the data obtained, it clearly shows that the influence of the Arabic method is still widely used in the Jawi writing system at that time, although there are some reforms, but it is still small compared with the Arab influence.